Physical chemistry and bromatological evaluation of four varieties of potato (Solamun spp.) - Obregón, Antonio (2013)
Were evaluated four native varieties of potato: yellow runtus (Solanum goniocalyx), huayro (Solanum chaucha), peruanita (Solanum goniocalyx Juz. & Bukasov) and huamantanga (Solanum tuberosum andigena), from the peruvian highlands, province of Huancayo, department of Junin. These potato varieties had an average diameter greater than 30 mm, with rounded and elongated shapes, having yellow and reddish skin. The dry matter content was 22,98 to 31,80%, showing a direct relationship with the specific gravity and the starch content (17,50 to 26,20%). The high content of starch and dry matter found, classified them as high quality tubers culinary, being suitable for the manufacture of dried products fried products. The dry samples, in grams percent, showed: total protein 6,75 to 10,54; ethereal extract 0,22 to 0,35; ash 2,23 to 3,79; raw fiber from 1,48 to 2,33; carbohydrates from 84,01 to 87,89; reducing sugars from 1,50 to 1,80; total acidity from 0,13 to 0,28; caloric value from 380,20 to 382,86 Kcal. Vitamin C content was 7,85 to 16,19 mg%. pH varied from 6,30 to 6,90.